Pengaruh Kualitas Air terhadap Keanekaragaman Plankton di Bozem: Analisis Parameter Fisik, Kimia, dan Biologi Ekosistem Perairan - Prana Nala Shekina; Nia Intan Ramadhani; Nayla Devi Putri; Septia Ajeng Kurniati; Cindy Evana Agustin (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Water quality plays an important role in maintaining the balance of aquatic ecosystems, including the abundance and diversity of plankton. This study aims to analyze the effect of various water quality parameters such as temperature, dissolved oxygen (DO), carbon dioxide (CO2) levels, Biochemical Oxygen Demand (BOD), pH, brightness, and turbidity on plankton diversity in Bozem. Data were obtained from eight observation stations with water quality parameter measurements and plankton sampling. The results showed that the water quality in Bozem was not optimal, with low DO values ​​(1.79 mg/L), high water temperatures (average 31.05°C), and low brightness (0.30 m), which contributed to the decline in plankton abundance. A total of 39 plankton genera were identified, with Synedra as the most dominant genus. Poor water quality inhibits plankton growth, which can impact the balance of the food chain in these waters. This study shows the importance of better water quality management to maintain the sustainability of aquatic ecosystems in Bozem. This study also contributes to the understanding of the multifactorial interactions between water quality parameters and plankton.